2016
DOI: 10.1186/s12879-016-1429-y
|View full text |Cite
|
Sign up to set email alerts
|

Are current case-finding methods under-diagnosing tuberculosis among women in Myanmar? An analysis of operational data from Yangon and the nationwide prevalence survey

Abstract: BackgroundAlthough there is a large increase in investment for tuberculosis control in Myanmar, there are few operational analyses to inform policies. Only 34 % of nationally reported cases are from women. In this study, we investigate sex differences in tuberculosis diagnoses in Myanmar in order to identify potential health systems barriers that may be driving lower tuberculosis case finding among women.MethodsFrom October 2014 to March 2015, we systematically collected data on all new adult smear positive tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
2
1
0
Order By: Relevance
“…This population-based Xpert MTB/RIF analysis followed expected gender distributions [ 21 ]; 70% of individuals diagnosed with Mtb were males, and overall, the proportion of males who were Mtb positive out of all males tested (47%) was higher than the proportion of females who were positive for Mtb (39%), replicating previous smaller scale regional reports from Myanmar [ 15 ]. Examination by age category revealed that Mtb test positivity differed significantly over life course with the highest proportion of individuals who tested positive for Mtb among those aged 16–20 (Fig.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…This population-based Xpert MTB/RIF analysis followed expected gender distributions [ 21 ]; 70% of individuals diagnosed with Mtb were males, and overall, the proportion of males who were Mtb positive out of all males tested (47%) was higher than the proportion of females who were positive for Mtb (39%), replicating previous smaller scale regional reports from Myanmar [ 15 ]. Examination by age category revealed that Mtb test positivity differed significantly over life course with the highest proportion of individuals who tested positive for Mtb among those aged 16–20 (Fig.…”
Section: Discussionsupporting
confidence: 77%
“…Recent scale up of in-country rapid testing capacity using a national network of Xpert MTB/RIF (Cepheid, Sunnyvale, CA, USA) linked to the Myanmar Data Utilization Project has further increased testing capacity and diagnosis of TB and MDR-TB. This expansion of national rapid diagnostic capability and connectivity provides a unique opportunity to explore the characteristics of TB disease by both age and sex, and to identify at-risk sub-populations for additional diagnostic targeting [ 15 18 ]. The primary aim of this study was to utilize the electronically captured data to uncover demographic risk factors and patterns associated with TB diagnosis and rifampicin resistance specific to Myanmar.…”
Section: Introductionmentioning
confidence: 99%
“…In our study, we found that women were more likely to use private providers, consistent with other research that also found that male TB patients outnumbered females in Yangon’s public health sector [ 23 ]. Evidence from other settings indicates that women may experience greater stigma from TB or challenges in travelling long distances to reach healthcare, and private providers may be perceived to allow greater patient privacy and be more conveniently located [ 24 – 26 ].…”
Section: Discussionsupporting
confidence: 91%